2011
DOI: 10.1088/0967-3334/32/11/003
|View full text |Cite
|
Sign up to set email alerts
|

A novel photoplethysmography technique to derive normalized arterial stiffness as a blood pressure independent measure in the finger vascular bed

Abstract: Stiffening of the small artery may be the earliest sign of arteriosclerosis. However, there is no adequate method for directly assessing small arterial stiffness. In this study, the finger arterial elasticity index (FEI) was defined as the parameter n which denotes the curvilinearity of an exponential model of pressure (P)-volume (V(a)) relationship (V(a) = a - b exp (-nP)). For the original estimation, the FEI was calculated from a compliance index from the finger photoplethysmogram whilst occluding the finge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The finger PPG was measured in the transmittance mode using an 810-nm near-infrared LED as the light source and a photodiode as the photo sensor, placed on opposite sides of the tip of the left middle finger. The sensors and an amplifier to which the sensors were connected were built in the authors' laboratory, as has been previously reported (Tanaka et al, 2011). A logarithmic transformation was applied to the NPV values (i.e., ln NPV) to normalize the distribution.…”
Section: Measurements and Devicesmentioning
confidence: 99%
“…The finger PPG was measured in the transmittance mode using an 810-nm near-infrared LED as the light source and a photodiode as the photo sensor, placed on opposite sides of the tip of the left middle finger. The sensors and an amplifier to which the sensors were connected were built in the authors' laboratory, as has been previously reported (Tanaka et al, 2011). A logarithmic transformation was applied to the NPV values (i.e., ln NPV) to normalize the distribution.…”
Section: Measurements and Devicesmentioning
confidence: 99%
“…It has been reported that the FEI reflects structural (not functional) changes in the finger artery [17], [19], and the PP is also known to change with age following the progressive stiffening of larger arteries [16]. For these reasons, FEI and PP are generally recognized as long-term cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although a definite reason for this is not yet clear, one possibility could be considered. According to Tanaka et al's measurement procedure [19], FEI is calculated from the average value of eight or nine measurements. Therefore, the one-shot measurement applied in the present prototype might be inadequate to evaluate the long-term elasticity of small arteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations